1997
DOI: 10.1111/1467-6281.00010
|View full text |Cite
|
Sign up to set email alerts
|

Information Provided by Accrual and Cash‐Flow Measures of Operating Activities

Abstract: This article examines accrual and cash-flow measures useful for observing companies' financing, investing and operating activities. It addresses the information provided jointly by income and operating cash flow, and reveals that information provided by these accounting measures is dependent on their relative magnitudes. A consistent pattern of income in excess of operating cash flow, with both measures appropriately adjusted and scaled, indicates superior company growth. Income and cash-flow patterns are asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 12 publications
2
20
0
1
Order By: Relevance
“…Higgins (1972) suggested that larger firms are more likely to pay higher dividends to shareholders than small firms because they have more flexibility in raising funds from capital markets. Similar positive relationships were noted in prior studies (e.g., Brockman & Unlu, 2009;Gugler, 1997;Ingram & Lee, 1997;Lloyd et al, 1985). Thus, it is hypothesised that: Hypothesis 2.…”
Section: Agency Cost Hypothesissupporting
confidence: 77%
See 1 more Smart Citation
“…Higgins (1972) suggested that larger firms are more likely to pay higher dividends to shareholders than small firms because they have more flexibility in raising funds from capital markets. Similar positive relationships were noted in prior studies (e.g., Brockman & Unlu, 2009;Gugler, 1997;Ingram & Lee, 1997;Lloyd et al, 1985). Thus, it is hypothesised that: Hypothesis 2.…”
Section: Agency Cost Hypothesissupporting
confidence: 77%
“…Meanwhile, Gugler (1997) contended that, in the US, large companies are inclined to pay dividends to prevent managers from investing for their own self-interest. Since small firms have to reinvest to grow, the funds available for dividend payouts would be reduced (Ingram & Lee, 1997). Brockman and Unlu (2009) found strong evidence of a positive relationship between the size of the firm and the dividend sizes of a large sample of firms across 52 countries, including emerging markets such as Malaysia.…”
Section: Sizementioning
confidence: 99%
“…The 1990 study by Charitou and Ketz, however, indicated that earnings were valued more than cash flows, and cash flows and accruals provide equal information in explaining security prices. Similar result was given by Ingram and Lee (1997);and Ali (1994) that used both linear and non-linear relationships when examining the incremental information content of earnings, working capital from operations and cash flows.…”
Section: Evidence On Incremental Information Content Of Cash Flowssupporting
confidence: 58%
“…Similar results were also found by [10] where it is shown that, on average, disaggregated earnings are better able to reflect value relevant events than disaggregated cash flows over return intervals of one to ten years. While many studies report evidence on the superiority of the accrual over the cash flow basis and vice versa, [12] approached this issue by examining both accrual and cash flow measures jointly in determining firms' performance. They found that, for companies having a consistent pattern of income in excess of operating cash flow, with both measures appropriately adjusted and scaled, indicates superior company growth.…”
Section: Introductionmentioning
confidence: 99%
“…As the sales increases, the payables and receivables will also increase but with a different magnitude. The offset is seldom complete because receivables generally change more rapidly than payables (due to the difference between selling and cost price), making the current assets increment being greater than the current liabilities increment [12] . For firms with operating growth, this situation is expected to persist, resulting in the gap between the payables and receivables becoming wider throughout the growth period.…”
Section: Introductionmentioning
confidence: 99%